Exposure to neonicotinoid pesticides induces physiological disorders and affects color performance and foraging behavior in goldfish - Izuru Kakuta; Kiyomi Takase (Physiological Reports, 2024)
Abstract We investigated the effects of neonicotinoid pesticides (NEOs) on the spontaneous swimming and foraging behavior, as well as the morphological and physiological changes of goldfish. Most fish reared in thiamethoxam (THM)‐sprayed rice fields showed the scales easily peeled off, and increased ascites. Some individuals showed decreased bio‐defense activity and low plasma Ca2+. Similar changes were found in the exposure test to THM (1.0 and 20.0 μg/L) and dinotefuran (1.2 and 23.5 μg/L). Next, the effects of a low concentration of THM (1.0 μg/L) on the spontaneous swimming and foraging behavior of fish were examined. Fish exposed to THM for 1 week became restless and had increased the swimming performance, especially under natural light, white LED lighting and blue LED lighting. Goldfish exposed to THM had also increased intake of shiny white beads under green LED illumination. These results indicate that the exposure to NEO, even for a short period and at low levels, not only suppressed bio‐defense activities and metabolic abnormalities, but also stress response, the swimming and foraging behavior of the fish are likely to be significantly suffered.